2021
DOI: 10.3390/arts10030047
|View full text |Cite
|
Sign up to set email alerts
|

External Shocks in the Art Markets: How Did the Portuguese, the Spanish and the Brazilian Art Markets React to COVID-19 Global Pandemic? Data Analysis and Strategies to Overcome the Crisis

Abstract: The spread of the COVID-19 pandemic worldwide, and the restrictions imposed by the social distance and the enforced confinement, are having an impact on the art markets globally. The aim of this article is to evaluate the impact of an external shock in the primary art market, using three countries as a case study: Portugal, Spain, and Brazil. These geographies have in common being at the margins in the art market’s main art hubs. It is intended to analyze how agents are responding to the new context, according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…The study also revealed how practitioners were forced to see the future of theatre and comedia in the light of digitalisation if there was any hope of salvaging the performing arts. In another study, Duarte et al (2021) pointed out how Portuguese, Spanish and Brazilian contemporary arts companies took to expanding digital activities, kept participating in art fairs hybrid models, continued to focus on internationalisation, and advocated the strengthening of public policies towards the sector and partnerships as key strategies to overcome the crisis.…”
Section: Revenue Related Challengesmentioning
confidence: 99%
“…The study also revealed how practitioners were forced to see the future of theatre and comedia in the light of digitalisation if there was any hope of salvaging the performing arts. In another study, Duarte et al (2021) pointed out how Portuguese, Spanish and Brazilian contemporary arts companies took to expanding digital activities, kept participating in art fairs hybrid models, continued to focus on internationalisation, and advocated the strengthening of public policies towards the sector and partnerships as key strategies to overcome the crisis.…”
Section: Revenue Related Challengesmentioning
confidence: 99%
“…Concerning the global art market's performance in relation to sustainability, its specific way of functioning-depending on a strong calendar of events, such as art fairs or exhibitions worldwide-makes the topic particularly challenging. On the other hand, the ability of the field to search for alternative measures, and the resistance to external shocks, has been a way of overcoming the complex issues in the sector [1]. In addition to the recent health pandemic crisis and the ongoing consequences of the Russian invasion of Ukraine, the art trade has found solutions as exploring hybrid models for buying and selling art, showing a prompt adaptation to the digital trade, and the online platforms developed by galleries and art fairs became more usual.…”
Section: Introductionmentioning
confidence: 99%
“…Adelaide Duarte, Ana Leticia Fialho, and Maria Perez-Ibanez have investigated the impact of the pandemic on the Portuguese, Spanish, and Brazilian art markets. They have highlighted the resilience to external shocks-such as COVID-19-faced by contemporary art galleries in these countries, which have manifested in two respects: their adaptability to "the impossibility of face-toface access, cancellation of exhibitions at their venues and participation in art fairs" and with regard to their quick adjustment to "an uncertain future in terms of the calendar of upcoming fairs, access to new markets and clients and new conditions in the commercial activity itself, with scarce support of public policies" (Duarte et al 2021).…”
mentioning
confidence: 99%